Sustainable food processing instrument (i-KProM) among Technical and Vocational Education Training (TVET) students - Suriani Mohamed (Tanjong Malim, 2021)
Sustainable food processing instrument (i-KProM) among Technical and Vocational Education Training (TVET) students by Suriani Mohamed